PENGARUH MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR EKONOMI KELAS X IIS SMA NEGERI 2 KUALA MANDOR B - yarso, Yanti; Aminuyati, Aminuyati; Sumarto, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of the study is the Effect of Student Learning Interest on Learning Outcomes in Economic Subjects in Class X IIS at SMA Negeri 2 Kuala Mandor B. This study aims to determine the effect of student learning interest on learning outcomes in economic subjects of class X IIS in SMA Negeri 2 Kuala Mandor B. The research method is used descriptive method quantitative research from. The data source of this study is students of class X IIS which amounted 30, and the data is the value of the results of the 1 day test in economics. Data collection tools use, interview guidelines, questionnaires, notebooks. The results of the study stated that students interest in learning with indicators of feeling good is included in both categories with a percentage of 81.78%, indicators of interenst are included in both categories with a percentage of 79.5%, indicator of attention included in both categories with a percentage of 78.76%, indicators of involvement are included in both categories with a percentage of 79.75%, and learning outcomes with indicators of daily test scores in economic subjects included in the complete category of 56.7% or 17students. And the influence of student interest in learning outcomes of class X IIS in SMA Negeri 2 Kuala Mandor B amounted to 14.7%. Keywords: Student Learning Interest, Learning Outcomes Â